Manajemen Pengembangan Peserta Didik Berbasis Total Quality Management di MI Al-Hidayah Bagor Miri Sragen - Dewi Isnawati Intan Putri (Millah: Journal of Religious Studies, 2020)
Students are an important element in education, without students it is impossible to develop in the classroom. This research was conducted at MI Al-Hidayah Bagor Sragen regency. This study aims to improve the quality of the students quality to have qualified abilities when completing studies at an  educational institution and implement the development of students based on total quality management (TQM) as an alternative in printing intelligent educational outputs of intellect and morality, one of the educational institutions implementing the management is MI Al-Hidayah Bagor Sragen regency. Researchers in researching MI Al-Hidayah used a qualitative approach with descriptive analysis. The results of this study are that in developing the quality of students requires good management also in developing students such as understanding the process and customer satisfaction, the madrasa will be able to realize and appreciate quality. Management of student development used by researchers namely Planning, mechanism for student acceptance, selection process and orientation activities for new students, division of classrooms, guidance and development, monitoring and evalation of student management in MI Al-Hidayah Bagor Sragen regency.Keywords: Students, Development, Management.